Stochastic Scheduling by the Horizon Method - Symonds, G. H. (Management Science, 1962)
The stochastic scheduling problem discussed in this paper is similar to the classical inventory model. It is concerned with the demand for a single commodity expressed as a set of independent stochastic variables with known distributions and an objective functional composed of production and inventory cost variables. The model, however, incorporates a uniquely determined planning horizon, and in the usual application requires only a finite number of time periods. The horizon period is based upon the minimum expected loss in the operation and therefore is subject to the stochastic variables of demand.